A Pain in the Neck. Issue 2 (1st June 2010) - Newstead, Dr Beth; Smith, JE
Abstract : Colonoscopy is a generally safe test whose use is rapidly increasing; complications are unusual and the accepted rate of perforation after diagnostic colonoscopy is between 1 in 800-1500 cases. Colonoscopic perforation may not be recognised at the time and the patient may present to a variety of medical practitioners after discharge from hospital. The presentation is usually with abdominal pain. We report an unusual presentation of colonoscopic perforation in which the patient attended the Emergency Department complaining of a painful neck.